Research on Packet Enhanced OTN Equipment and Networking - Ming Cheng; Zhou Zhou; Jun Zhu; Jun Zhang (Dianxin kexue)
As a converged technology, the packet enhanced optical transport network（POTN/PE-OTN）technology is able to meet the rapidly growing demand for bandwidth and multi-service bearing with differentiated quality of services. The statuses of POTN/PE-OTN technology standards were introduced. The architecture of POTN/PE-OTN equipment and the possible implementations were analyzed. The architecture of networking with POTN/PE-OTN technology in the metropolitan area network was discussed.